Pyrodinium bahamense and other dinoflagellate cysts in surface sediments of Cancabato Bay, Leyte, Philippines - Yap-Dejeto, Leni; Durante, Caryl Y.; Tan, Irene L.; Alonzo, Coleen O. (2018)
Cysts withstand hostile environmental conditions and are source of inoculum for recurrent blooms. In the Philippines, the first recorded bloom of the phytoplankton Pyrodinium bahamense was observed in Samar-Leyte areas, including Cancabato Bay in 1983. Since then, shellfish bans in these areas have been imposed periodically. Until the present however, there is no thorough cyst study done in this bay. This study has assessed the abundance and distribution of dinoflagellate cysts in the bay. Surface sediment samples collected and processed by palynological technique have revealed a total of 21 species of dinoflagellate cysts belonging to five groups: Gonyaulacoid, Protoperidinioid, Gymnodinioid, Calciodinellid, and Diplopsalid. Cysts have been detected in all stations, with cyst densities ranging from 1-80 cysts g-1 DW; and Operculodinium centrocarpum (Protoceratium reticulatum) dominated in four stations. Low levels of P. bahamense cysts, Polysphaeridium zoharyi, have been detected in 13 stations, the densest at 16 cysts g-1 DW. Concentrations of cysts that have been highest in the inner part of the bay could have been affected by several factors, including substrate type, bulk dry weight, and nitrogen content. This important stage of the lifecycle of dinoflagellates should be factored in future models to predict P. bahamense blooms in the bay.